PENGARUH FINANCIAL CONSTRAINT TERHADAP AGRESIVITAS PAJAK DI MASA PANDEMI DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Putri Shyeefa A'alia; Nurul Aisyah Rachmawati (Jurnal Akuntansi dan Keuangan, 2022)
The research aims to determine the effect of financial constraints on tax aggressiveness in pandemic times with independent commissioners as moderation variables. This study uses the OLS (Ordinary Least Square) method. The population in the study was a Manufacturing Company listed on the Indonesia Stock Exchange in 2020 with a sample number of 92 taken using purposive sampling methods. This study found that financial constraint variables had a positive and significant effect on tax aggressiveness variables in pandemic times. Independent commissioner variables reinforce the positive influence between financial constraints and tax aggressiveness in pandemic times. This study was only conducted in 2020 during the covid 19 pandemic phenomenon so the research data could not provide a comparison of the company's condition before the pandemic.